Synthesis, Structural Determination and Antibacterial Properties of Zinc(II) Complexes Containing 4-Aminopyridine Ligands - Dewi Mariyam; Ubed Sonai Fahruddin Arrozi; Sugiarto Sugiarto; I Wayan Dasna; Husni Wahyu Wijaya (Universitas Gadjah Mada, 2023)
Three zinc(II) complexes containing 4-aminopyridine (4-NH2py) [Zn(4-NH2py)2(NCS)2] (1), [Zn(4-NH2py)2Cl2] (2), and [Zn(4-NH2py)2(NCS)Cl] (3) were synthesized and characterized by FTIR and single crystal X-ray diffraction. All complexes adopt a slightly distorted tetrahedral geometry with different crystal packing. Complex 1 crystallizes in the orthorhombic Pmmn space group, complex 2 in the monoclinic C2/c space group, and complex 3 in the orthorhombic Pbca space group. Non-covalent interactions such as NC-S···H, -Cl···H, and µ-µ stacking interaction between 4-NH2py and other ligands (NCS− and Cl−) are observed in the crystals packing. In vitro, antibacterial screening of all complexes was evaluated against two bacteria (Escherichia coli and Staphylococcus aureus). The results show that 1 has the highest antibacterial activity than 2 and 3. This difference is due to differences in the interactions elicited by the anion ligands.